Robben Island 1591-1920 - Smith, Pam M (Library and Information Studies Centre (LISC), 2015)
This bibliography on Robben Island covers the known history of the Island from its earliest discovery until 1920 when the Infirmary for lepers, lunatics and the chronically ill was finally abandoned. The bibliography does not claim to be exhaustive: illustrations and government publications have been excluded and no systematic search of newspapers was undertaken because of lack of time; newspaper articles are recorded only where the compiler was guided there by other references. The Cape Town archives contain a large number of documents - mainly official correspondence - which could not be included in this limited work, but which are relative to the Island's history. Annotations concerning the scope and content of the material have been made in nearly all cases. It was found to be impracticable to annotate certain of the works as fully as the others because of the vast amount of information they contained on all aspects of the Island's history. These works are Van Riebeek's journal, Theal's Histories, Moodie's Records and Leibbrandt's precis of the archives of the Cape of Good Hope.